Polycarbonate-based biodegradable copolymers for stimuli responsive targeted drug delivery. Issue 25 (7th June 2016) - Ganivada, Mutyala Naidu; Kumar, Pawan; Kanjilal, Pintu; Dinda, Himadri; Sarma, Jayasri Das; Shunmugam, Raja
Abstract : The newly developed polymeric nanocarrier could open a new avenue for cancer therapy, due to its unique design as well as, most importantly, its biocompatible and biodegradable nature. Abstract : The need for efficient nanoscale polymeric systems that elegantly target cancer-affected areas in the body has arisen, since drug efficacy is mostly disturbed by nonspecific cell and tissue biodistribution. Motivated by the challenges, we have developed a novel tumour-targeting polymeric nanocarrier using polylactide and polycarbonate as the polymeric backbone. Biotin and doxorubicin are covalently attached to the poylmeric backbone using a combination of ring opening polymerisation and click chemistry. All the monomers and polymers are characterised carefully through standard analytical techniques. The self-assembly behaviour of these copolymers is studied through DLS and FE-SEM analysis. Doxorubicin release from the copolymer backbone is pH-dependent owing to the unique oxime linker. Cell culture studies of the biotin and doxorubicin-conjugated nanocarrier [Bt-(PE-PA-PC)-DRoxm ] exhibited higher intracellular doxorubicin accumulation at cancer cells. The newly developed polymeric nanocarrier could open a new avenue for cancer therapy, due to its unique design as well as, most importantly, its biocompatible and biodegradable nature.